Estimation of Total Yearly CO2 Emissions by Wildfires in Mexico during the Period 1999–2010 - Flor Bautista Vicente; Noel Carbajal; Luis Felipe Pineda Martínez (Advances in Meteorology)
The phenomenon of wildfires became a global environmental problem which demands estimations of their CO2 emissions. Wildfires have deteriorated the air quality increasingly. Using available information on documented wildfires and a data set of satellite detected hot spots, total yearly emissions of CO2 in Mexico were estimated for the period 1999–2010. A map of the main vegetation groups was used to calculate total areas for every vegetation type. The yearly number of hot spots per vegetation type was calculated. Estimates of emitted CO2 in a wildfire were then accomplished by considering parameters such as: forest fuel load, vegetation type, burning efficiency, and mean burned area. The number of wildfires and total affected areas showed an annual variability. The yearly mean of affected area by a single wildfire varied between 0.2 and 0.3 km2. The total affected area during the period 1999 to 2010 was 86800 km2 which corresponds to 4.3% of the Mexican territory. Total CO2 emissions were approximately 112 Tg. The most affected vegetation types were forest and rainforest.